2017
DOI: 10.18632/oncotarget.20763
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3-inflammasome inhibition prevents high fat and high sugar diets-induced heart damage through autophagy induction

Abstract: The NLRP3-inflammasome complex has emerged as an important component of inflammatory processes in metabolic dysfunction induced by high-caloric diets. In this study, we investigate the molecular mechanisms by which NLRP3 inhibition may attenuate diet-induced cardiac injury. Here we show the cardiac damage induced by high sugar diet (HSD), high fat diet (HFD) or high sugar/fat diet (HSFD) over 15 weeks. Genetic ablation of NLRP3 protected against this damage by autophagy induction and apoptotic control. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 46 publications
(54 reference statements)
4
32
1
Order By: Relevance
“…Meanwhile, our present data also revealed that the activation of NLRP3 inflammasome triggered by LPS and ATP induced the activation of autophagy in Caco-2 cells, which is consistent with the previous study showing that NLRP3 inflammasome activation could induce mitophagy/autophagy in peritoneal mesothelial cells [45]. On the contrary, several evidences illustrate that inhibiting NLRP3 inflammasome would trigger autophagy activation [46]. Hence, it is necessary to identify the precise relationship between NLRP3 inflammasome activation and autophagy activation.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, our present data also revealed that the activation of NLRP3 inflammasome triggered by LPS and ATP induced the activation of autophagy in Caco-2 cells, which is consistent with the previous study showing that NLRP3 inflammasome activation could induce mitophagy/autophagy in peritoneal mesothelial cells [45]. On the contrary, several evidences illustrate that inhibiting NLRP3 inflammasome would trigger autophagy activation [46]. Hence, it is necessary to identify the precise relationship between NLRP3 inflammasome activation and autophagy activation.…”
Section: Discussionsupporting
confidence: 91%
“…mTOR is a serine‐threonine kinase that functions as an intracellular energy sensor whose genetic and pharmacological inhibition has been shown to extend life in a wide range of organisms (Cordero, Williams, & Ryffel, ; Wu et al, ). Since it is known that mTOR induces autophagy, the ablation of NLRP3 also showed, consistent with previous data showing the effect of inhibition of NLRP3 with other stressors, such as a hypercaloric diet, an increase in autophagy during aging (Pavillard et al, ). Cardiac aging is characterized by the presence of hypertrophy, fibrosis, and the accumulation of misfolded proteins and dysfunctional mitochondria.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, NLRP3‐deficient mice have been reported to exhibit significant protection from high fat diet‐induced metabolic syndrome, characterized by reduced sterile inflammation (i.e., a decrease in the frequency of effector T cell infiltrate in visceral adipose tissue), reduced adipocyte hypertrophy and liver steatosis, and preservation of pancreatic β‐cell mass that results in improved insulin sensitivity and glucose tolerance . A number of studies have now largely confirmed this pathogenic role for NLRP3 and ASC in obesity‐related disorders, such as insulin resistance and Type 2 diabetes, nonalcoholic steatohepatitis (NASH) and cardiovascular disease (e.g., atherosclerosis) …”
Section: Nlrp3 In Health and Diseasementioning
confidence: 97%